Assessing local capacity to expand rural breast cancer screening and patient navigation: An iterative mixed-method tool. (April 2017) - Inrig, Stephen J.; Higashi, Robin T.; Tiro, Jasmin A.; Argenbright, Keith E.; Lee, Simon J. Craddock
Highlights: Longitudinal, iterative, mixed-method tools facilitate accurate capacity assessment. Hub-and-spoke delivery models can effectively extend rural access to funding. Success relies on program flexibility and rapid response to changes in capacity. Contracts, competition, existing protocols, and willingness to accept new patients impact program uptake. Abstract: Background: Despite federal funding for breast cancer screening, fragmented infrastructure and limited organizational capacity hinder access to the full continuum of breast cancer screening and clinical follow-up procedures among rural-residing women. We proposed a regional hub-and-spoke model, partnering with local providers to expand access across North Texas. We describe development and application of an iterative, mixed-method tool to assess county capacity to conduct community outreach and/or patient navigation in a partnership model. Methods: Our tool combined publicly-available quantitative data with qualitative assessments during site visits and semi-structured interviews. Results: Application of our tool resulted in shifts in capacity designation in 10 of 17 county partners: 8 implemented local outreach with hub navigation; 9 relied on the hub for both outreach and navigation. Key factors influencing capacity: (1) formal linkages between partner organizations; (2) inter-organizational relationships; (3) existing clinical service protocols; (4) underserved populations. Qualitative data elucidate how our tool captured these capacity changes. Conclusions: Our capacity assessment tool enabled the hub to establish partnerships with county organizations by tailoring support to local capacity and needs. Absent a vertically integrated provider network for preventive services in these rural counties, our tool facilitated a virtually integrated regional network to extend access to breast cancer screening to underserved women.